Use of Allopurinol to Mitigate 6-Mercaptopurine Associated Gastrointestinal Toxicity in Acute Lymphoblastic Leukemia - Conneely, Shannon E.; Cooper, Stacy L.; Rau, Rachel E. (Frontiers in Oncology, 2020)
An essential component of acute lymphoblastic leukemia (ALL) therapy is the prolonged maintenance phase with daily 6-mercaptopurine (6-MP) as the cornerstone. While 6-MP is generally well-tolerated, some patients suffer from significant side effects such as gastrointestinal (GI) toxicity, including hepatitis, hypoglycemia, nausea and pancreatitis, which can substantially limit the tolerated dose of 6-MP. These toxicities are thought to result from skewed metabolism of 6-MP leading to an accumulation of the 6-methylmercaptopurine (6-MMP) metabolite. Here we describe current knowledge behind the use of allopurinol to modify 6-MP metabolism and improve tolerance to therapy. This method has been successfully used in adults with inflammatory bowel disease refractory to purine therapy and has been modified for use in children with GI toxicities related to 6-MP in maintenance therapy for ALL. Use of allopurinol for 6-MP related toxicities should be reserved for patients in which an alternative cause of signs or symptoms has been excluded and for whom non-pharmacologic measures have failed. When allopurinol is used, simultaneous dose reduction of 6-MP is required to avoid severe myelosuppression and related side effects, though overall combination therapy appears to be well tolerated and effective when instituted appropriately.